2016
DOI: 10.1002/etc.3337
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐mediated climate susceptibility in a warming world: Larval and latent effects on a model amphibian

Abstract: Although sophisticated models predict the effects of future temperatures on ectotherms, few also address how ubiquitous sublethal contaminants alter an organism's response to thermal stress. In ectotherms, higher metabolic rates from warming temperatures can beneficially speed metabolism and development. If compounded by chronic, sublethal pollution, additional resource demands for elimination or detoxification may limit their ability to cope with rising temperatures-the toxicant-induced climate susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Despite the concern that trace metals become more toxic at higher temperatures , and the potential of strong delayed effects of metals during and after metamorphosis (see above), delayed interactive effects between metals and warming have been largely ignored. The only exception are two studies showing delayed sublethal effects of previous exposure to metals being magnified under warming (for adult body mass: ref , for juvenile body condition: ref ). Here, we showed that also across metamorphosis delayed effects of a metal can be magnified under warming, and even translated in a synergistic lethal effect by shortening adult lifespan.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the concern that trace metals become more toxic at higher temperatures , and the potential of strong delayed effects of metals during and after metamorphosis (see above), delayed interactive effects between metals and warming have been largely ignored. The only exception are two studies showing delayed sublethal effects of previous exposure to metals being magnified under warming (for adult body mass: ref , for juvenile body condition: ref ). Here, we showed that also across metamorphosis delayed effects of a metal can be magnified under warming, and even translated in a synergistic lethal effect by shortening adult lifespan.…”
Section: Resultsmentioning
confidence: 99%
“…This strong postmetamorphic lethal effect of zinc complements the very few documented adverse metal effects across metamorphosis: lowered survival in bryozoans, 14 lowered fecundity in mosquitoes, 60 lowered immune function and delayed reproduction in flies, 27 and reduced body condition in juvenile frogs. 28 Although some elimination of metals can happen during metamorphosis (e.g., via the shed larval skins), metal body burdens after metamorphosis can still remain very high. 61,62 Moreover, in addition to the stress that metamorphosis itself creates, the remobilization of stored metals during tissue reorganization at metamorphosis has been suggested to magnify the effects of metals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic and antimony concentrations in water, sediment, primary producers, and tadpoles at sites HS, CP, and OP were previously quantified; detailed descriptions of methods and results were provided in 2016 in the work of Dovick et al 12 For the present study, we quantified As and Sb concentrations in water and sediment samples collected during the middle of our sampling schedule (day 185), using the protocol described in the Dovick et al work 12 and in tadpole samples collected on each site visit using protocols described below. To account for the known effects of water temperature on tadpole growth and development, 14 including interactions with contaminants, 15 we deployed a water temperature data logger (32K StowAway Tidbit −5 °C to 37 °C logger, Onset Computer Corp., Bourne, MA, USA) in each site at a shoreline used by tadpoles. We placed a solar radiation shield over each logger to prevent direct sunlight from reaching the device through the shallow (ca.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Organisms in polluted environments are typically exposed to a cocktail of stressors. Trace metals are, for instance, omnipresent in freshwater ecosystems; and combined with the effects of global warming they can be harmful at low concentrations to aquatic organisms including fish (Noyes and Lema 2015), amphibians (Hallman and Brooks 2016), and insects such as damselflies (Debecker et al 2017). This is attributable to the fact that environmental warming increases the body temperature of ectothermic animals and will alter physiological and biochemical reactions but also will affect the stability of biological molecules (Sokolova and Lannig 2008).…”
Section: Introductionmentioning
confidence: 99%